2014
DOI: 10.1007/s00167-014-3473-8
|View full text |Cite
|
Sign up to set email alerts
|

Tibial ACL insertion site length: correlation between preoperative MRI and intra-operative measurements

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…All these approaches have the aim to optimize restoration of the native ACL and its tibial insertion site. Previous studies reported pre-and intraoperative measurements of the length of the tibial insertion site [14,28]. However, considering that the shape of the tibial insertion site varies, the area of the tibial insertion site is required to ensure proper planning of graft size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these approaches have the aim to optimize restoration of the native ACL and its tibial insertion site. Previous studies reported pre-and intraoperative measurements of the length of the tibial insertion site [14,28]. However, considering that the shape of the tibial insertion site varies, the area of the tibial insertion site is required to ensure proper planning of graft size.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative measurements of the insertion site can be conducted easily using a customized ruler [21]. It was shown that preoperative determination of the length of the tibial insertion site using MRI is possible as well [28]. Furthermore, it could be shown that the size of the graft can be determined preoperatively using MRI measurements [5].…”
Section: Introductionmentioning
confidence: 99%
“…As part of this concept, the graft size should match the individual patient’s anatomy so as to avoid postoperative complications such as graft impingement, high failure rate, and poor patient‐reported outcome scores [6, 8, 23, 24, 29–31, 38, 44]. Accurate preoperative assessment of potential autograft size [notably, the cross‐sectional area (CSA)] aids in assuring that the dimensions of the native ACL can be adequately recapitulated with reconstruction [16, 21, 42, 46].…”
Section: Introductionmentioning
confidence: 99%
“…Midsagittal and midcoronal T1 MRI sequences can be used to measure the size of the tibial footprint, ACL length, inclination angle, and thickness of potential autograft donor sites including the patellar, quadriceps, and hamstring tendons (Figure 2) [43][44][45]. Additional oblique coronal and sagittal sequences assist in identifying partial or single-bundle ACL injuries (Figure 3) [46,47].…”
Section: Preoperative Considerationsmentioning
confidence: 99%